The dynamics of atheization in postwar communist Montenegro - Lakić, Todor (Poligrafi, 2025)
This article presents the concept and dynamics of secularization policies and the atheization process in Montenegrin society following World War II. The pro-cess of secularization began with the Communist party’s rise to power and had its most significant manifestations until the mid-1950s. In this research, in addition to the specific secularization policies of the communist authorities, an analysis of the relationship of the state, that is, the communist authorities, towards the religious communities in Montenegro is given. Montenegro was the Yugoslav republic in which the process of atheization and secularization took place most intensively in relation to the federal level. The research presented in the article also includes an analysis of the results of the secularization of the three largest religious commu-nities in Montenegro.
Keywords: ateizem; atheism; communism; Črna gora; komunizem; Montenegro; religious communities; secularization; sekularizacija; verske skupnosti